2nd Symposium of Lasers in Dentistry - Marques, Marcia Martins; Marques, José Luiz Lages; Gomes, Anderson; Gonçalves, Sergio Eduardo de Paiva; Oliveira, Marcella Esteves (Brazilian Dental Science, 2016)
.